INVESTIGATING THE EFFECTIVENESS OF ROBOT-ASSISTED STEM EDUCATION: A MULTILEVEL META-ANALYSIS (European Journal of Interdisciplinary Research and Development, 2025)
This study investigates the effectiveness of robot-assisted STEM education through a multilevel meta-analysis method. Scientific articles published between 2010 and 2022 were analyzed. The findings confirm the positive impact of robotics on improving students’ academic achievement, enhancing their attitude towards learning, and developing computational thinking skills. Furthermore, moderator factors such as teacher support, level of interactivity, subject area, education level, and duration of instruction were identified as influencing effectiveness. The results can inform both practical and theoretical recommendations for improving the organization of robot-assisted STEM education